2007
DOI: 10.1177/153303460700600203
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation of Renal Cancer: Variables Involved in Freezing-Induced Cell Death

Abstract: The detection of renal tumors has increased significantly over recent years resulting in a greater demand for novel, minimally invasive techniques. Cryoablation has emerged as a valuable treatment modality for the management of renal cancer. In an effort to detail the effects of freezing in renal cancer, the human renal cancer (RCC) cell line, 786-O, was evaluated in vitro. 786-O cells were exposed to a range of freezing temperatures from -5 to -40 degrees C and compared to non-frozen controls. The data show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 40 publications
4
52
1
1
Order By: Relevance
“…16,[26][27][28] The PaCa response was similar to the À20 C isotherm reported for renal carcinoma. 36 For both prostate and renal cancer, decreasing levels of survival have been reported following exposure to À15…”
Section: Discussionmentioning
confidence: 99%
“…16,[26][27][28] The PaCa response was similar to the À20 C isotherm reported for renal carcinoma. 36 For both prostate and renal cancer, decreasing levels of survival have been reported following exposure to À15…”
Section: Discussionmentioning
confidence: 99%
“…However, the delayed effect resulting from damage to the microvasculature of the renal parenchyma is believed to be the most important mechanism of action of cryoablation [16]. Majority of times, the repeated cycles of freezing and thawing enhances tissue destruction, with some animal model experiments showing evidence that double freezing lead to large areas of tissue destruction compared to single freezing [17] …”
Section: Cryotherapymentioning
confidence: 99%
“…However, it is believed that the important mechanism of action of cryoablation is the delayed effect resulting from damaging the microvasculature of the renal parenchyma [16]. In the majority of the time, repeated cycles of freezing and thawing enhances tissue destruction with some evidence from animal model experiments showed that double freezing led to large areas of tissue destruction compared to single freezing [17]. During treatment, the temperature achieved is typically between −20 and −40°C or lower.…”
Section: Cryotherapymentioning
confidence: 99%